Comparative Dissolution Study of Different Brands of Amoxicillin Trihydrate Capsules Available in Bangladesh (Stamford Journal of Pharmaceutical Sciences, 2010)
Commercially available twenty national and four multinational brands of Amoxicillin Trihydrate capsules werestudied  in water  for 60 minutes using USP reference dissolution apparatus. All, except  two national brands(Code: NB-8 and NB-15); complied with  the USP  in vitro dissolution specification  for drug release (not  lessthan 80% of the labelled amount of amoxicillin trihydrate should be dissolved in 60 minutes). Drug releasesfrom those two brands were 75% and 67% respectively within the specified time period. Key words: In vitro Dissolution; Market preparations; Amoxicillin Trihydrate; Capsule; National Brand;Multinational Brand.DOI: 10.3329/sjps.v2i2.5827Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 72-75